Effect of ZnO-Saturated Electrolyte on Rechargeable Alkaline Zinc Batteries at Increased Depth-of-Discharge. Issue 6 (27th March 2020) - Lim, Matthew B.; Lambert, Timothy N.; Ruiz, Elijah I.
Abstract : Rechargeable alkaline batteries containing zinc anodes suffer from redistribution of active material due to the high solubility of ZnO in the electrolyte, limiting achievable capacity and lifetime. Here, we investigate pre-saturating the KOH electrolyte with ZnO as a strategy to mitigate this issue, utilizing rechargeable Ni–Zn cells. In contrast to previous reports featuring this approach, we use more practical limited-electrolyte cells and systematically study ZnO saturation at different levels of zinc depth-of-discharge (DODZn ), where the pre-dissolved ZnO is included in the total system capacity. Starting with 32 wt. % KOH, cells tested at 14%, 21%, and 35% DODZn with ZnO-saturated electrolyte exhibit 191%, 235%, and 110% longer cycle life respectively over identically tested cells with ZnO-free electrolyte, with similar energy efficiency and no voltage-related energy losses. Furthermore, anodes cycled in ZnO-saturated electrolyte develop more favorable compact zinc deposits with less overall mass loss. The effect of initial KOH concentration was also studied, with ZnO saturation enhancing cycle life for 32 wt % and 45 wt % KOH but not for 25 wt % KOH, likely due to cell failure by passivation rather than shorting. The simplicity of ZnO addition and its beneficial effect at high zinc utilization make it a promising means to make secondary alkaline zinc batteries more commercially viable.